2016
DOI: 10.1155/2016/8797086
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Cognitive Control System in Recovery from Bilingual Aphasia: A Multiple Single-Case fMRI Study

Abstract: Aphasia in bilingual patients is a therapeutic challenge since both languages can be impacted by the same lesion. Language control has been suggested to play an important role in the recovery of first (L1) and second (L2) language in bilingual aphasia following stroke. To test this hypothesis, we collected behavioral measures of language production (general aphasia evaluation and picture naming) in each language and language control (linguistic and nonlinguistic switching tasks), as well as fMRI during a namin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
1
15
0
1
Order By: Relevance
“…Age of acquisition, immersion, and self-evaluation of language use was assessed using a custom-made questionnaire ( Radman et al, 2016 ). We assessed immersion in French and English by asking the following information: the AoA, how long they lived in a region where the dominant spoken language was English or French, which language they spoke with their family members, in school, in present activities (watching TV/listening to radio, reading books, arithmetic), and if the language was acquired in school or out of school only.…”
Section: Methodsmentioning
confidence: 99%
“…Age of acquisition, immersion, and self-evaluation of language use was assessed using a custom-made questionnaire ( Radman et al, 2016 ). We assessed immersion in French and English by asking the following information: the AoA, how long they lived in a region where the dominant spoken language was English or French, which language they spoke with their family members, in school, in present activities (watching TV/listening to radio, reading books, arithmetic), and if the language was acquired in school or out of school only.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-language treatment effects have been reported for a substantial number of multilingual PWA who vary in their lesion size and site, which makes drawing clear conclusions about the role of the lesion site in determining response to treatment challenging. Nevertheless, several treatment studies have proposed evidence for impaired control mechanisms and consequent effects on response to treatment [55][56][57].…”
Section: Lesion Sitementioning
confidence: 99%
“…One suggestion for future investigations is to employ neuroimaging techniques to study patients with bilingual aphasia because of the possibility to reveal cross‐domain effects of plasticity after language recovery. For instance, some studies have shown increased connectivity within the network involved in language control specifically for the language that was successfully recovered …”
Section: Overlap Between Ec and Blc Networkmentioning
confidence: 99%